2019
DOI: 10.1080/21691401.2019.1601103
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Association of the polymorphisms in FOXO1 gene and diabetic nephropathy risk

Abstract: Purpose: This study was aimed to study the hypothesis that forkhead box O1 (FOXO1) gene rs17446614 and rs17592236 single nucleotide polymorphisms (SNPs) influenced the development of diabetic nephropathy (DN). Methods: This study included 138 DN patients and 149 healthy controls. Controls were matched with the patients in age and gender. The method of polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLP) was used to detect FOXO1 gene polymorphisms. Haploview software was conducted to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The FoxO1/rs2297626 A allele and the AA genotype showed significantly increased frequencies in acute anterior uveitis patients with ankylosing spondylitis [29]. The FoxO1/rs17592236 located in 3′-UTR of the FoxO1 gene and the identified Ars17446614-Crs17592236 haplotype were associated with an increased risk of diabetic nephropathy [30]. Considering these studies, we selected nine single nucleotide polymorphisms (SNPs) in Th17/Treg cell-related genes, including IL2RA, miR27a, miR182, and FoxO1, to explore the association between gene polymorphisms and GD susceptibility in Southwest Chinese Han population.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The FoxO1/rs2297626 A allele and the AA genotype showed significantly increased frequencies in acute anterior uveitis patients with ankylosing spondylitis [29]. The FoxO1/rs17592236 located in 3′-UTR of the FoxO1 gene and the identified Ars17446614-Crs17592236 haplotype were associated with an increased risk of diabetic nephropathy [30]. Considering these studies, we selected nine single nucleotide polymorphisms (SNPs) in Th17/Treg cell-related genes, including IL2RA, miR27a, miR182, and FoxO1, to explore the association between gene polymorphisms and GD susceptibility in Southwest Chinese Han population.…”
Section: Introductionmentioning
confidence: 95%
“…Based on the available literature studies, we selected nine SNPs, which were earlier shown to be associated with a variety of autoimmune diseases [25][26][27][28][29][30]. Finally, we selected three SNPs (rs3118470, rs2104286, and rs7093069) for IL2RA, one SNP (rs895819) for miR27a, one SNP (rs76481776) for miR182, and four SNPs (rs2297626, rs17592236, rs9549241, and rs12585277) for FoxO1.…”
Section: Selection Of Single Nucleotide Polymorphismsmentioning
confidence: 99%
“…However, the exact mechanism regarding the pathophysiology of DKD remains unclear [7]. Clinical and epidemiological studies have shown that there is a family history of DKD in various ethnic groups, suggesting that genetic factors play a key role in developing the disease [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine FOXO1 gene is located on chromosome 13q14.11 and encodes the FOXO1 protein, which belongs to the FOXO family. FOXO1 could combine with a promoter by shuttling into the nucleus and activate the transcription activity of the target genes [40]. FOXO1 plays multiple important roles in regulating cell homeostasis, glucose metabolism, immune response, cell cycle progression, apoptosis, and aging [14,15].…”
Section: Discussionmentioning
confidence: 99%